A Tale of Two Crises in Peru: Livelihoods and Social Reproduction During the 1980s and the COVID-19 Pandemic - Vincent, Susan; Clark, Patrick; Chanca Flores, Aparicio (Anthropologica, 2022)
The COVID-19 pandemic has wreaked havoc on the livelihoods of people around the world. Structural economic constraints are highlighted at such moments of crisis, while those most affected have recourse to their repertoire of managing strategies. This case study of people from Allpachico, a Peruvian peasant community, compares their responses to the current crisis with their responses to one in the 1980s, showcasing similarities in strategies (especially reciprocity and the sale or exchange of necessary reproductive tasks and products) and differences in the form they take. In the 1980s, women’s work and kin reciprocity helped people access use-values. By 2020, neoliberalism had transformed the national economy and Allpachiqueño migrants overwhelmingly had precarious informal and contract work. Reciprocity and reproductive tasks are still central to livelihood, but now tend to be monetized rather than involving use-values. As that earlier crisis shattered both secure employment and peasant farming to lay the basis for neoliberalism, so now it appears that the COVID-19 pandemic, through the monetization of government support and reciprocity alike, is accelerating financialization in the form of financial services and debt.